Teknologi Formulasi Rhizobakteria Berbasis Bahan Lokal dalam Menunjang Bioindustri Pertanian Berkelanjutan - Ashifa Cahyani; Muh. Ichsan Putrayani; Hasrullah Hasrullah; Muh. Ersyan; Tita Aulia S.; Abdul Mollah Jaya (Hasanuddin University, 2017)
Food as the main of human needs. So, all the sectors that could suppport the advance of plant productivity should be concerned, such as by using the right applied methods. Plant productivity could be increased by fixing their physicology responses to spur plant growth. The using of chemical substances to spur the plant growth have to be switched by using biofertilizer as an alternative through formulation technology of Rhizobacteria based on local materials to support agricultural bioindutry. In the root there are beneficials bacteria which are involved in Plant Growth Promoting Rhizobacteria (PGPR) that could increase the ability of root to absorb soil nutrient and plant hormones synthesis naturally. Endophytics bacteria are founded in the certain of plants root could be isolated and manipulated into biofertilizer product. Generally there are 3 steps in the making process of PGPR : starter making, nutrient making, and fermentation. In this reasearch the endophytics bacteria are isolated from leguminosae root which has a symbiotic with Rhizobium sp., maize (Zea mays sp.) root and bamboo (Bambusa sp.) root which has a symbiotic with Bacillus sp. dan Pseudomonas sp. PGPR utilizes microbacteria as a biological agens that could keep the availability of soil nutrients and increase quality and healthy of soil (soil remediator). In addition of the microbacteria function are : to produce antibiotics, patogen competitor, and to produce plant growth hormone which support plant physicological process.Keywords: Endophytic Bacteria, Biofertilizer, Food, PGPR, Rhizobacteria